EP.WE.162Correct consenting for Vascular Patient. (28th October 2021) - Khalaf, Hasan; Behbahani, A.; Walsh, Aideen
Abstract: Introduction: Surgeons must establish and maintain effective relationships with patients and, where appropriate, with their supporters. Before surgery, surgeons should strive to have an honest and sensitive discussion with patients about their options for treatment that leads to informed and deliberate consent. The aim of this study is to compare our consent practice in the vascular department in Royal Stoke Teaching Hospital against consent guideline in the Best surgical practice and to if we are meeting patient satisfaction. Method: A prospective study of 30 patients from 21/09/2020 to 21/10/2020. Questionnaire form was designed based on the best surgical practice guideline and was given to the patient to fill. We include patients admitted for elective vascular procedures, wide range ages. The questionnaire Results: Most of the of the patient (90%) were consented by the professionals who provide the treatment. 63% of the patients asked for further information in the form pf leaflets or websites. 70% of them request to know the recent guidelines of their procedures. Only 13% of them had a copy of the consent prior to surgery. Recommendations: We must provide the patients with further information, Recent guidelines, and a copy of the consent to take home prior to surgery day. This can be achieved by consenting them before the operation day.